The effect of the simple fitness exercise model to improve the vocational students’ physical fitness - Ahmad Ridwan; Farid Imam Nurhadi; Betrix Teofa Perkasa Wibafied Billy Yachsie; Ahmad Nasrulloh; Nurmanita Rismaningsih (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
Physical fitness is needed by every human being to support his activities. Vocational Students are no exception when entering the industrial world. Because people who have good physical fitness will not feel tired quickly and still have other energy reserves to continue other activities. Vocational students who are basically required to have 70% skills must a healthty and fit body. As for the research objective, namely to determine the effect of the simple fitness training model to improve the physical fitness of Vocational students. The population of this research is vocational students with a sample of 24 students. The sampling technique uses a purposive sample with the criteria of final semester Indonesian Traditional Medicine Study Program students who are willing to take part in the study. This study uses mix of methods (qualitative and quantitative) with qualitative using the literature review and quantitative using the two group pretest and posttest design approach. Data were collected using the focus discussion grup and Cooper test instrument to determine cardiopulmonary fitness and the push-up sit-up test to determine the endurance of the arm and abdominal muscles. The results showed that the simple fitness training model had an effect on the physical fitness of vocational students with an average increase of 16%, the abdominal and arm muscle endurance groups by 15%. Based on the result of the sit up test and push up test. With the existence of a simple fitness training model, it can be carried out and is useful for students, especially vocational students.